Himpunan Mahasiswa Jurusan dan Matrikulasi Bahasa Arab bagi Mahasiswa Baru - Muhammad Jundi; Muhammad Zikran Adam; Ibadurrahman Ali; Suleman D. Kadir; Siti Aliyya Laubaha (Naskhi: Jurnal Kajian Pendidikan dan Bahasa Arab, 2022)
Arabic matriculation is an additional course program provided by the Arabic Education Department to new students to equalize their basic Arabic language skills. This program is better known among students as the Afternoon Course, where the Student Association plays a role in succeeding it. Therefore, this research aims to embrace the role of the Student Association in Arabic matriculation programs for new students. This research is descriptive with a qualitative approach where data collection techniques are interviews, observations, and documentation. Data begins to be analyzed during data collection based on the data analysis process by Miles and Huberman, namely: data reduction, data presentation, and data collection. The results showed 1) In the implementation of afternoon course matriculation, the department and the student associations established beneficial cooperation and good relations between the two parties. 2) The role of the student association in the program includes recruitment of tutors, pretesting, scheduling, implementation of learning, and evaluation. 3) The motivation of students to become tutors is to seek experience and as a forum for teaching exercises. The benefit they get when they become a tutor is that it helps improve their teaching skills. Further research is needed on the effectiveness of the matriculation program on participants' Arabic language skills and the effect of the program on the teaching ability of tutors.